The PhoBR two-component system regulates antibiotic biosynthesis in Serratia in response to phosphate - Gristwood, T; Fineran, P; Everson, L; Williamson, N; Salmond, G (BioMed Central, 2009)
Background: Secondary metabolism in Serratia sp. ATCC 39006 (Serratia 39006) is controlled via a complex network of regulators, including a LuxIR-type (SmaIR) quorum sensing (QS) system. Here we investigate the molecular mechanism by which phosphate limitation controls biosynthesis of two antibiotic secondary metabolites, prodigiosin and carbapenem, in Serratia 39006. Results: We demonstrate that a mutation in the high affinity phosphate transporter pstSCAB-phoU, believed to mimic low phosphate conditions, causes upregulation of secondary metabolism and QS in Serratia 39006, via the PhoBR two-component system. Phosphate limitation also activated secondary metabolism and QS in Serratia 39006. In addition, a pstS mutation resulted in upregulation of rap. Rap, a putative SlyA/MarR-family transcriptional regulator, shares similarity with the global regulator RovA (regulator of virulence) from Yersina spp. and is an activator of secondary metabolism in Serratia 39006. We demonstrate that expression of rap, pigA-O (encoding the prodigiosin biosynthetic operon) and smaI are controlled via PhoBR in Serratia 39006. Conclusion: Phosphate limitation regulates secondary metabolism in Serratia 39006 via multiple inter-linked pathways, incorporating transcriptional control mediated by three important global regulators, PhoB, SmaR and Rap.